The minimum employee’s salary in the Iraqi Legislation: Comparative Study - عبد القادر بان صلاح; صالح سجى كريم (Journal of Legal Sciences, 2019)
The subject of "The minimum employee’s salary in the Iraqi Legislation" is a significant and practical importance for discussing the minimum range for salary as one of the important guarantees that approved by legislator in the civil law service and related laws based on the relied criteria and concepts that participate to decide that point. All that shall fit with general economical status and considering its development by routine viewing and increasing it based on the employee’s status and his general position. This research will state the position of Iraqi legislator of reporting and adjusting the minimum range of employee’s salary and comparing it with the status of Egyptian and Lebanese legislators.